2009
DOI: 10.1509/jmkg.73.2.55
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Experience on the Web: An Empirical Examination of Consumer Behavior for Search and Experience Goods

Abstract: By lowering the costs of gathering and sharing information and offering new ways to learn about products before purchase, the Internet reduces traditional distinctions between search and experience goods. At the same time, differences in the type of information sought for search and experience goods can precipitate differences in the process through which consumers gather information and make decisions online. A preliminary experiment shows that though there are significant differences in consumers' perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
405
0
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 590 publications
(424 citation statements)
references
References 74 publications
9
405
0
10
Order By: Relevance
“…For example, Girard, Silverblatt, and Korgaonkar (2002) found that consumers have greater willingness to shop from an Internet retailer for search products than experience products; Girard and Dion (2010) validated the product classification framework online and confirmed that the risk of experience goods is significantly higher than that of search goods; Huang, Lurie, and Mitra (2009) found that consumers view fewer pages but spend more time per page before purchasing experience goods than search goods.…”
Section: Product Type and Pricementioning
confidence: 88%
“…For example, Girard, Silverblatt, and Korgaonkar (2002) found that consumers have greater willingness to shop from an Internet retailer for search products than experience products; Girard and Dion (2010) validated the product classification framework online and confirmed that the risk of experience goods is significantly higher than that of search goods; Huang, Lurie, and Mitra (2009) found that consumers view fewer pages but spend more time per page before purchasing experience goods than search goods.…”
Section: Product Type and Pricementioning
confidence: 88%
“…Neste sentido, Huang et al (2009), ao avaliar as comunidades virtuais na visão do marketing, pode concluir que elas possibilitam aos clientes aprenderem com as experiências de outras pessoas e conseguirem dados sobre produtos e vivências. Apesar de comunidade virtual indicar que estas são menos reais que as comunidades tradicionais, para os grupos sociais envolvidos, elas têm presença real e influenciam no comportamento e no consumo de seus …”
Section: Dossiê -Competitividade Das Destinações Turísticasunclassified
“…In mobile e-commerce, potential consumers search for product information before making purchasing decisions due to the overwhelming information [8,12,16]. Since search could reflect consumers' purchase intentions and affect their choices online [9], it is worthy of deep exploration and has attracted a lot of interest from both academia and practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…In marketing practice, clickstream data are commonly used to quantify the customers' search behaviors [8,9,16]. Usually, the clickstream data provide information about the sequence of pages or the path viewed by the consumers as they navigate websites [18].…”
Section: Introductionmentioning
confidence: 99%